Fenomena Adat Larangan Pernikahan Dengan Posisi Rumah Ngalor-Nguolon Di Desa Kalipahit Kabupaten Banyuwangi - Eko Setiawan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This study aims to analyze the history and description of the custom prohibition of ngalor-ngulon marriage. Using Alfred Schutz's theory, the cause motive and the goal motive, a rational action is value-oriented. Every action taken refers to the values of salvation and blessing of life. This research uses a qualitative approach based on facts in the field obtained through observation, in-depth interviews, documentation. Data analysts use interactive models. The results showed that the ban on ngalor-ngulon marriage is still firmly held by the community. Although some people do not believe in these taboos because they are not in accordance with religious teachings or only as mere suggestions. The youth do not pay much attention to the abstinence of ngalor-ngulon, obeying this tradition only because they respect the requests of their parents and respect for their ancestors.